Potensi Pembelajaran Berbasis Etnosains dalam Buku Ajar Kurikulum Merdeka IPA SMP Kelas VII - Dinurrohmah, Syayidah; Sari, Greny Mispi Anisa; Wisutama, Remanda Arya; Sulaeman, Nurul Fitriyah; Nuryadin, Atin (Universitas Hamzanwadi, 2023)
The context of ethnoscience-based learning in the Merdeka curriculum is related to socio-cultural studies. Following up on the uncommon science learning integrated with ethnoscience studies, especially in the socio-cultural realm, a content analysis of textbooks used in schools was conducted. This study aims to determine the potential of junior high school science learning using the Merdeka curriculum integrated into ethnoscience studies in the socio-cultural aspect. The research was conducted using the content analysis method, with the analyzed indicators consisting of 5 parts of values in socio-cultural. The results showed that science learning has great potential to be integrated with ethnoscience studies, considering that the textbooks have been able to present all value indicators in the socio-cultural. All indicators have been contained in the book in each chapter, except for spiritual value incarcerates. The appearance of all indicators in each chapter in the book provides information on the suitability of textbooks with the aim of curriculum. However, spiritual value indicators are still contained in only 2 chapters in the book, so it is necessary to strengthen spiritual values in each chapter in the book. Further research can be done by conducting content analysis with a more diverse number of books, so as to provide a broader picture of textbooks